Looking down on human intelligence from psychometrics to the brain - Deary, Ian J.; Oxford eBooks (Oxford : Oxford University Press, 2000)
What is it about human brains that makes some people more capable than others? In this critical account, Professor Ian Deary reviews historical, cognitive, and biological research on the foundations of human mental ability.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intellect; Electronic books